Impaired function of regulatory T-cells in patients with chronic obstructive pulmonary disease (COPD) - Tan, D.; Fernandez, S.; Price, Patricia; French, M.; Thompson, P.; Moodley, Y. (Urban and Fischer Verlag, 2014)
Anti-inflammatory pathways affecting chronic obstructive pulmonary disease (COPD) are poorly understood. Regulatory T-cells (Tregs) are important negative regulators of T-cell activity and hence were investigated in COPD patients in this study. We hypothesised that functional defects in Tregs may promote increased inflammation contributing to the pathogenesis of COPD.Peripheral blood mononuclear cells (PBMC) were isolated from patients with stable COPD and age-matched non-smoking controls. Treg-mediated suppression of memory non-Treg (Foxp3-CD45RO+) CD4+ T-cell activation was analysed by comparing PBMC responses to staphylococcal enterotoxin-B (SEB) pre- and post-depletion of Tregs (CD25+CD127lowCD4+ T-cells) by fluorescence-activated cell sorting (FACS). Activation of T-cells was assessed by HLA-DR expression. Levels of secreted cytokines were measured by ELISA.Depletion of Tregs increased SEB-induced activation of Foxp3-CD45RO+ CD4+ T-cells in samples from 15/15 healthy controls (demonstrating Treg-mediated suppression) and 9/14 COPD patients (Fisher's test, p = 0.017). A screen of clinical data associated a failure of Treg-mediated suppression in the remaining five COPD patients with a higher body mass index (BMI) (33–38 kg/m2) compared to patients with unimpaired Treg function (20–32 kg/m2).In conclusion, we demonstrate impaired Treg-mediated suppression of CD4+ T-cell activation in a subset of COPD patients, all of whom had high BMI. Obesity and/or perturbed homeostasis of Treg subsets may explain this defect and therefore contribute to increased inflammation observed in COPD.